Plankton of Karwar Waters with Remarks on the Hydrographic Conditions and Fishery - U.G., Naik; C.R., Reddy; D.C., Shetty; B., Neelakantan (Fishery Technology, 2025)
The results obtained from the investigations on the abundance and seasonal Â fluctuations of plankton and hydrographic conditions of fishing areas cf Karwar waters are presented and discussed. The displacement volume of plankton (9.2-29.6 ml/m3) showed two peaks one in November-December and other in February-March. Among the phytoplankton, the diatoms constitute the major part of the total phytoplankton with dominant species like Fragillaria, Coscinodiscus, Thalassiothrix, Chaetoceros, Nirzschina, Rhizosolenia and Biddulphia whereas among the zooplanktons, the dominant groups mainly comprised of copepods, decapod larvae, chaetognaths and medusae. The observed valuis ofhydrographic parameter showed a bimodal peak. A correlation between plankton abundance and fishery has been attempted in this paper.